Optimization of Reduced Glutathione Production by a Lactobacillus plantarum Isolate Using Plackett–Burman and Box–Behnken Designs - Al-Madboly, Lamiaa A.; Khedr, Eman G.; Ali, Safaa M. (Frontiers in Microbiology, 2017)
In this work, we aim to optimize the production of reduced glutathione (GSH) synthesized intracellularly by a food-grade microorganism through a statistical approach. Using a colorimetric method, 25 Lactobacillus plantarum isolates were screened in an attempt to find a GSH-producing strain. It was found that thirty six percent of the tested isolates showed positive result. Isolate (L7) was found to produce 152.61 µM glutathione per gram which was the highest amount produced intracellularly. Accordingly, the later isolate was selected for the optimization process using Plackett-Burman and Box-Behnken designs. Temperature, amino acids and urea were found to be the most significant independent variables. Following data analysis, the composition of the optimized medium was De Man-Sharp-Rogosa broth as a basal medium supplemented with Na Cl (5%), H2O2 (0.05 %), sodium dodecyl sulphate (0.05 %), amino acids (0.0281 %), and urea (0.192 %). The pH of the medium was adjusted to 8 and incubated for 24 h at 40 oC. The GSH amount was increased by 10-fold (851 %) using the optimized medium. Hence, our optimization design estimated the biotechnological potential of L. plantarum (L7) for the production of GSH in the industry